Corporate Governance, CEO Compensation and Accounting Conservatism - Alexandros Sikalidis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: This study examines the moderating impact of corporate governance quality on the relation between CEO bonus compensation and accounting conservatism. Design/methodology/approach: We use market-based and accrual-based measures to estimate accounting conservatism. According to prior literature (Core, Holthausen and Larcker, 1999; Bhojraj and Sengupta, 2003; Rees and Rodionova, 2015), agency and managerial self-interest theory state that corporate governance strength can mitigate the negative relation between CEO bonus compensation and accounting conservatism. Finding: Our sample consists of S&P 500 companies while our empirical findings suggest that CEO bonus compensation and accounting conservatism are positively associated. Research limitations/implications: Thus, our results do not provide clear evidence about the direction of the effect of strong corporate governance. Both measures of accounting conservatism do not give significant relations, therefore the results about corporate governance strength are contradicting. The results hold the same after controlling for industry-specific effects. Originality/value: The purpose of this study is to shed light to the literature of accounting conservatism, corporate governance and CEO compensation. Furthermore, this research examines the current situation of corporate governance and motivates future improvement of corporate governance mechanisms.
Keywords: G3; M12; M4; 330; Corporate Governance; Executive Compensation; Accounting and Auditing